2004
DOI: 10.1162/1535351041747996
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of SARS: The Case of Hong Kong

Abstract: SARS is the first deadly infectious disease of the 21st century. It started in the Chinese province of Guangdong in November 2002, and by August 2003, it had spread to 29 countries and 3 regions, with a cumulative total of 8,422 cases and 916 deaths. This paper describes the spread of the disease in Hong Kong and discusses its impact on the economy. SARS was an unexpected negative shock. The most significant negative effects were on the demand side, with local consumption and the export of services related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(149 citation statements)
references
References 1 publication
4
141
0
4
Order By: Relevance
“…We see that the effect is the largest using 2000-2002 data: a 10-unit increase in API will lead to a 3.13% increase in the CVR mortality rate (Column 1). Using data from more recent years, we find the air pollution effect on CVR mortality rate becomes smaller and statistically insignificant (Hung, 2003;Siu & Wong, 2004). Particularly, it unveiled some basic failings of HK's healthcare 12 Year 2003 data are dropped from this analysis because several hundred people died from SARS, but these deaths are unrelated to air pollution.…”
Section: Air Pollution Effects Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…We see that the effect is the largest using 2000-2002 data: a 10-unit increase in API will lead to a 3.13% increase in the CVR mortality rate (Column 1). Using data from more recent years, we find the air pollution effect on CVR mortality rate becomes smaller and statistically insignificant (Hung, 2003;Siu & Wong, 2004). Particularly, it unveiled some basic failings of HK's healthcare 12 Year 2003 data are dropped from this analysis because several hundred people died from SARS, but these deaths are unrelated to air pollution.…”
Section: Air Pollution Effects Over Timementioning
confidence: 99%
“…Nearly three hundred people died from SARS, but these deaths were not related to air pollution. In addition, during the SARS epidemic, economic activities and daily life of people in HK were significantly changed (Hung, 2003;Siu & Wong, 2004). For example, most people used face masks and avoided going outside during the outbreak, which could affect pollution exposure and reduce their chances of contracting other types of respiratory diseases.…”
Section: Mortality Datamentioning
confidence: 99%
“…Lee and McKibbin [28] claimed that it had resulted in a US$40 billion loss to the world, especially for China and Hong Kong. In addition, Siu and Wong [29] reported that its impacts were negative, albeit short term, and on economic demand rather than supply. During the outbreak of H1N1 influenza, also known as "swine flu", the world economy experienced a 0.34% loss [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the low prevalence of SARS in the general population, the public strongly eschewed restaurants, shopping centers, and other public places (Chou et al, 2004;Siu and Wong, 2004). The high infection rate in hospitals also caused people to avoid the health care system: outpatient visits fell by 31% in April and May of 2003 (Hsieh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%